Chemical constituents isolated from the ethyl acetate extract of the roots of garcinia atroviridis - Nur Salsabila, Ahmad Roslan (2020)
Several preliminary studies on the roots of Garcinia atroviridis have reported on their antibacterial and antioxidant properties, which might be contributed by various bioactive secondary metabolites. Chemical compounds in the roots of G. atroviridis were isolated from ethyl acetate extract as the solvent was reportedly efficient for extraction of phenolic compounds with intermediate polarity. Thus, this study aims to isolate, purify, elucidate the phenolic compounds, and evaluate the biological properties of ethyl acetate extract and its isolated compounds. In addition, preliminary investigation on biological activity of other extracts extracted with different polarities of solvent was also conducted. The roots of G. atroviridis collected from Maran, Pahang were subjected to solvent extraction with different polarities of solvents. Preliminary biological screening was done on ethyl acetate extract to investigate the antibacterial and antioxidant activities. This extract was chosen because, the chemical investigation on this extract leads to the isolation of various phenolic compounds with various bioactivities as proven in previous studies. Ethyl acetate extract showed antibacterial activity against Gram-positive bacteria, Bacillus cereus and Staphylococcus aureus, in disc diffusion experiment. Significant total phenolic content (TPC) was identified in ethyl acetate extract using Folin-Ciocalteu (FC) reagent method, with a value of 568.6 ± 25.724 mg GAE/g. Upon further investigation with α, α-diphenyl-β-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays, ethyl acetate extract showed moderate antioxidant activities with IC50 of 51.7 ± 2.180 µg/mL and 294.0 ± 20.173 mg AAE/g, respectively. Based on antibacterial and antioxidant activities exhibited by ethyl acetate extract, further chemical investigation was carried out to isolate the phenolic compounds in the extract using silica gel column chromatography (Si gel CC) and preparative thin layer chromatography (PTLC). Five compounds were isolated namely atrovirisidone (7), morelloflavone (12), GB1a (18), 1,3,5- trihydroxy-2-methoxyxantone (29), and volkensiflavone (33). Volkensiflavone (33) was reported for the first time in G. atroviridis. Several spectroscopy techniques were used to elucidate the structure of isolated compounds, such as mass spectrometer (MS), ultraviolet-visible (UV-Vis), fourier-transform infrared (FTIR), and 1D- nuclear magnetic resonance (NMR) spectroscopy. Biological assays were conducted to all isolated compounds except atrovirisidone (7) due to limited yield. GB1a (18) and volkensiflavone (33) inhibited the growth of S. aureus as observed in antibacterial test. Morelloflavone (12) showed the highest DPPH scavenging activity with IC50 of 20.3 ± 1.667 µg/mL which was comparable to ascorbic acid (AA) with IC50 of 13.2 ± 0.021 µg/mL. In general, all compounds showed significant reducing power, of which 1,3,5-trihydroxy-2-methoxyxantone (29) demonstrated the highest FRAP activity with a value of 1643.3 ± 44.623 mg AAE/g. In addition, preliminary biological screening of different solvent extracts from the roots of G. atroviridis revealed the pharmaceutical potential of butanol extract, which showed the highest antibacterial and antioxidant activities. Correlation between phenolic content in root extracts of G. atroviridis and antioxidant activity was evaluated. Strong positive correlation between TPC and the measured capacity in DPPH (r = 0.8760) and FRAP (r = 0.9385) assays signified the role of phenolic compounds in antioxidant activity in root extract of G. atroviridis. In conclusion, antibacterial and antioxidant activities in root extract of G. atroviridis may be attributable to the presence of phenolic compounds.